Legal Power of Proof of Auction Minutes Deed in Electronic Implementation - Maskanah, Ummi; Nurhasanah, Siti; Avshary, Muhammad Akhmal (Manunggal Halim Jaya, 2025)
Auction is basically an act of buying and selling, where there are elements of price and goods, the difference is that the auction requires the presence of an auction official, with the stipulation of PMK 122/2023 concerning the implementation of electronic auctions, the auction can be carried out without the presence of an auction official, with the absence of the auction official contradicting the validity and strength of the auction minutes deed which still creates doubts for the auction winner in the implementation of the electronic auction. This study uses normative legal research that analyzes applicable laws and regulations and is applied in certain legal problems by analyzing laws and regulations relating to legal protection and electronic auctions, the results of the study obtained are the validity and legal force of the auction minutes deed can still be accepted as an authentic deed because it can be accounted for and the truth of the authentic deed by the auction official without deviating from the provisions of applicable laws and regulations.